University Students’ Learning Disruption and Affordance in a Contested Learning Environment - Siti Nur'Aini (Research in Social Sciences and Technology, 2021)
This study investigates how university students engage with their learning affordances in a contested environment due to the Coronavirus pandemic. This qualitative research employed a case study approach involving 136 participants. Data analysis was conducted using qualitative analysis as a circular process to describe, classify, and perceive the phenomenon and how the learning, affordances, and society were interconnected. The main framework of the research was the theory of affordance and how it was available for university students in their learning environment that changed due to the COVID-19 pandemic. Data were collected in the first semester of 2020 through an online survey on Google form. The findings indicate the importance of the social environment to provide affordance for the students to adjust with them. Four kinds of affordances emerged from the study; internet affordance, assignment affordance, domestic affordance, and distance learning affordance. The role of the social environment is definitive in changing how students manage their affordances.